Unsaturated properties of recycled concrete aggregate and reclaimed asphalt pavement - Rahardjo, Harianto (2013)
Construction and demolition of buildings together with the reconstruction of roads and pavements produce a lot of crushed concrete and asphalt waste. Problems associated with the disposal of these waste materials can be solved by recycling them for geotechnical engineering purpose. Recycled concrete aggregate and reclaimed asphalt pavement can be used as replacement for natural aggregates in road constructions, landfill capping systems, retaining walls, drainage works and slope protections. Many studies have been carried out to study the characteristics of recycled materials under saturated conditions. However, only few studies have been conducted to study the water characteristic curve (WCC) and permeability of recycled materials under unsaturated conditions. In addition, the shear strength of recycled materials under unsaturated conditions has not been fully investigated. Therefore, this paper focuses on the unsaturated properties of recycled materials, in particular, wetting WCC, wetting permeability function and unsaturated shear strength of recycled materials. In addition, the drying WCC, drying permeability function and saturated shear strength of recycled materials are also discussed. The experimental data of wetting WCC of recycled materials are compared with the predicted wetting WCC obtained using published equations. The experimental data of the saturated and unsaturated shear strength of recycled materials are fitted with nonlinear shear strength equations. In general, the investigated recycled materials have similar characteristics with natural aggregates under saturated and unsaturated conditions. The finer recycled concrete aggregate and reclaimed asphalt pavement have smaller particles sizes, higher water-entry values, lower permeability, lower values of minimum ϕ’ at failure and maximum ϕb as compared with the coarser recycled concrete aggregate and reclaimed asphalt pavement.